Serum vitamin D level in newly detected tuberculosis-a case control study - Thambi, Neethu; Vadakkedath, Achuthhan; Shafeekk, Muhammad; Kottarath, Manoj Dehandath; Mavila, Rajani; Veetil, Padmanabhan Kadammar (International Journal of Research in Medical Sciences, 2022)
Background: Vitamin D has a significant role in host immune defence against Mycobacterium tuberculosis. It has been suggested that pulmonary tuberculosis may be associated with lower levels of vitamin D. Present study was undertaken to identify the association between vitamin D deficiency and tuberculosis. Methods: A case-control study was conducted in a tertiary care hospital, including 25 adult newly diagnosed tuberculosis patients as cases and 25 age and sex-matched healthy participants as control groups. All participants in the study group had undergone detailed clinical examination and routine laboratory investigations, including vitamin D level estimation. The clinical characteristics, investigations including vitamin D levels were analysed and compared with data obtained from healthy controls. Results: Majority of the study population were in the age group of 40-50, with a mean age of 46.6±14.2. There were 20 pairs of males and 5 pairs of females. Out of the cases, 18 patients had pulmonary tuberculosis while 7 had extra pulmonary tuberculosis. Nine of the cases (36% of study population), 4 (16%) of the controls were underweight. The 15 (60%) of the cases and 20 (80%) of the controls were in the normal range and 1 case and 1 control were in the pre obese range. A total of 17 cases (68%), 8 controls (32%), had some degree of vitamin D deficiency (p=0.011) which is significant and suggests an association between the two. Conclusions: The prevalence of vitamin D deficiency in pulmonary tuberculosis cases is very high.